Floristic associations and filtering ability of riparian vegetation strips = Asociaciones florísticas en franjas de vegetación ribereña y sus capacidades de filtrado - Giaccio, Gustavo Carlos María; Laterra, Pedro; Cabria, Fabian Nestor (Fundación Rómulo Raggio, 2022)
The analysis of lateral flow runoff of superficial nutrients and sediments from an agricultural origin and their retention by infiltration of riparian vegetation strips are of great importance in reducing the agricultural externalities on surface water quality. The aim of this study was to relate soil infiltration to the main biophysical properties of riparian environments in the Pampa Austral of Argentina, defined by the composition of its plant community and the coverage of exotic species. We explored the relationships between hydraulic conductivity (Ks ) and aboveground, litter and root biomasses, organic matter concentration, terrain slope, soil bulk density, texture and electrical conductivity. We determined eight floristic associations through the classification of 65 censuses of vegetation. Three of the associations were dominated by native grasses, three by exotic grasses and two presented a layer of exotic willow trees in combination with native and invasive grasses. The mean Ks in soils from the floristic associations with trees and from the associations of native grasses without trees were higher than in soils from the associations of exotic grasses without trees. Significant relationships were found between Ks and the soil properties that are sensitive to the influence of vegetation, suggesting that the relationships between floristic composition and infiltration could be explained partly due to causal relationships.